Historical dictionary of international relations - Lamb, Peter, 1960- (Historical dictionaries of international organizations series (Unnumbered), 2017)
The Historical Dictionary of International Relations contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 200 cross-referenced entries on real world operations of international relations, the actual relations between states, organizations, groups and people.